(untitled) (American Journal of Pedagogical and Educational Research, 2026)
This study focuses on improving the methodology for developing cognitive processes in preparatory group children. Cognitive development at this stage plays a crucial role in shaping children’s readiness for school and their future learning abilities. The research highlights modern pedagogical approaches, interactive methods, and innovative techniques that enhance thinking, memory, attention, and problem-solving skills. Special emphasis is placed on play-based learning, visual aids, and integrated activities that stimulate children’s intellectual growth. The study also analyzes the role of teachers in organizing effective learning environments and guiding children’s cognitive development. As a result, practical recommendations are provided to improve educational practices in preschool institutions and ensure the holistic development of children.